Mechanical design - Childs, Peter R. N.
This book introduces the subject of total design, and introduces the design and selection of various common mechanical engineering components and machine elements. These provide "building blocks", with which the engineer can practice his or her art.The approach adopted for defining design follows that developed by the SEED (Sharing Experience in Engineering Design) programme where design is viewed as "the total activity necessary to provide a product or process to meet a market need." Within this framework the book concentrates on developing detailed mechanical design skills in the areas of be.